Kinetoplastid Genomics and Beyond - Requena, Jose M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes a collection of eight original research articles and three reviews covering a wide range of topics in the field of kinetoplastids. In addition, readers can find a compendium of molecular biology procedures and bioinformatics tools.